Experimental Testing of New Concrete-Based, Medium-Temperature Thermal Energy Storage Charged by Both a Thermal and Electrical Power Source - Raffaele Liberatore; Daniele Nicolini; Michela Lanchi; Adio Miliozzi (Energies)
This study aims to explore a new concept for a Power to Heat (P2H) device and demonstrate its effectiveness compared to a thermal heating method. The proposed concept is a medium-temperature system where electro-thermal conversion occurs via the Joule effect in a metallic tube (resistive element). This tube also serves as a heat exchange surface between the heat transfer fluid and the thermal storage medium. The heat storage material here proposed consists of base concrete formulated on purpose to ensure its operation at high temperatures, good performance and prolongated thermal stability. The addition of 10%wt phase change material (i.e., solar salts) stabilized in shape through a diatomite porous matrix allows the energy density stored in the medium itself to increase (hybrid sensible/latent system). Testing of the heat storage module has been conducted within a temperature range of 220–280 °C. An experimental comparison of charging times has demonstrated that electric heating exhibits faster dynamics compared to thermal heating. In both electrical and thermal heating methods, the concrete module has achieved 86% of its theoretical storage capacity, limited by thermal losses. In conclusion, this study successfully demonstrates the viability and efficiency of the proposed hybrid sensible/latent P2H system, highlighting the faster charging dynamics of direct electrical heating compared to conventional thermal methods, while achieving a comparable storage capacity despite thermal losses.